2007
DOI: 10.1210/me.2006-0300
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of a Conserved Serine in the Deoxyribonucleic Acid Binding Domain of Nuclear Receptors Alters Intracellular Localization

Abstract: Nuclear receptors (NRs) are a superfamily of transcription factors whose genomic functions are known to be activated by lipophilic ligands, but little is known about how to deactivate them or how to turn on their nongenomic functions. One obvious mechanism is to alter the nuclear localization of the receptors. Here, we show that protein kinase C (PKC) phosphorylates a highly conserved serine (Ser) between the two zinc fingers of the DNA binding domain of orphan receptor hepatocyte nuclear factor 4alpha (HNF4al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
1
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 85 publications
1
104
1
6
Order By: Relevance
“…It has been reported that HNF4␣ is under the control of various kinases (PKC and PKA) (38,39) and the role of ERK1/2 in the regulation of HNF4␣ has also been reported (40,41). This latter study suggested that the decreased endogenous HNF4␣ protein level due to various stimuli led to down-regulation of the expression of the target gene.…”
Section: Discussionmentioning
confidence: 81%
“…It has been reported that HNF4␣ is under the control of various kinases (PKC and PKA) (38,39) and the role of ERK1/2 in the regulation of HNF4␣ has also been reported (40,41). This latter study suggested that the decreased endogenous HNF4␣ protein level due to various stimuli led to down-regulation of the expression of the target gene.…”
Section: Discussionmentioning
confidence: 81%
“…Recently, estrogen receptor alpha (ERa) phosphorylated at the corresponding serine 216 was also found in mouse neutrophils and appears to regulate their infiltration into the uterus (Shindo et al, 2013). Although their phosphorylation in tissues in vivo have not yet been confirmed, studies with phosphomimetic mutants suggest that these residues in hepatocyte nuclear factor 4 alpha (HNF-4a), vitamin D receptor (VDR), peroxisome proliferator-activated receptor alpha, retinoid X receptor alpha (RXRa), and farnesoid X receptor may regulate various functionalities of these nuclear receptors, such as cytoplasmic retention, degradation, and transactivation (Hsieh et al, 1993;Sun et al, 2007;Gineste et al, 2008). Therefore, conserved phosphorylation has provided us with the opportunity to uniformly investigate nuclear receptors but has only been studied as the target of PKC or dephosphorylation by PP2A.…”
Section: Introductionmentioning
confidence: 99%
“…However, the corresponding residue in the AR subgroup of steroid receptors is alanine and is Ala-586 in human AR. PKC phosphorylation at Ser-78 in the DNA binding domain of hepatocyte nuclear factor-4␣ and other nuclear receptors regulates nuclear localization (60). Hepatocyte nuclear factor-4␣-S78A bound DNA, but the S78D phosphomimetic did not.…”
Section: Discussionmentioning
confidence: 97%